Evaluation of the validity and reliability of the 10-meter walk test using a smartphone application among Japanese older adults - Saito, Yoshinobu; Nakamura, Sho; Tanaka, Ayumi; Watanabe, Ryo; Narimatsu, Hiroto; Chung, Ung-il (Frontiers in Sports and Active Living, 2022)
Objective: Maintaining or improving regular walking speed can help extend healthy life expectancy and prevent frailty. The evaluation of walking speed can help individuals meet their daily exercise goals; therefore, it may be beneficial as a public health policy for residents to measure and evaluate their walking speed easily. This study aimed to verify the validity and reliability of a smartphone application for the 10-m walk test, measured in the general population. Methods: The study participants were men (n= 20) and women (n= 20) aged 65–85 years. The 10-m walk tests were performed at the usual walking speed, using the stopwatch function of a newly developed smartphone application. A total of three 10-m walk tests were performed simultaneously with the study participants and professional fitness instructors to evaluate the criterion-related validity and the test-retest reliability. Results: A strong positive correlation was found in the criterion-related validity by the study participants and professional staff for the average of the three trials (r = 0.961 [95% confidence interval CI = 0.927, 0.979]). The results revealed good reliability, with an intraclass correlation coefficient of 0.712 (95% CI = 0.571, 0.823). Conclusion: The smartphone application walking speed measurement method can be widely used by the general public and is useful for health promotion.